Shopper’s preferences towards shopping mall: a study at Plaza Kotaraya / Syed Khamarrulariffin Syed Jaffar - Syed Jaffar, Syed Khamarrulariffin (2010)
The purpose of this study is to find shoppers’ preferences towards shopping mall that study Plaza Kotaraya and the respondent are the shoppers of Plaza Kotaraya itself. The problem that Plaza Kotaraya faces is the decreasing number of shoppers patronizing the shopping mall. The objectives of this research are to identify the level of shoppers’ preferences towards Plaza Kotaraya, to rank the most dominant factors of shoppers’ preferences towards shopping mall and lastly to give recommendation to increase the number of shoppers to Plaza Kotaraya. For the research methodology, researcher used Exploratory and Descriptive Research in conducted this research study. The populations in this study are the shoppers of Plaza Kotaraya. Convenience Sampling is used as sampling technique. The number of respondent is 50 respondents. In this study, primary data is used to collect data using survey data collection method, which is questionnaire and mall intercept interviews. Data collected will analyze using Statistical Package for the Social Science (SPSS) for Windows. The methods will use Reliability Test and Frequency Distribution Analysis. For Reliability Test, Cronbach’s Alpha will use to measure the consistency reliability of data. Frequency Distribution Analysis will use to find frequency of respondents’ profile which it describes the frequency characteristics of the respondents. The finding for identifying the level of shoppers’ preferences towards Plaza Kotaraya is 3.64. For the result to rank the most dominant factors of shoppers’ preferences towards Plaza Kotaraya, entertainment is the factors that most affecting the shoppers’ preferences towards shopping mall.